Gravitational Scalar Field in 5-dimensional Kaluza-Klein Spacetime - Loan, Nguyen Ha (Communications in Physics, 2011)
In this work the results obtained earlier by the other authors for Gravitational Scalar Fields related to Generally Covariant Duality are extended for the case of Kaluza-Klein Unification model. The equations for these fields are derived explicitly by the use of tetrad postulate and their relation to the scalar field in the metric is considered.